Phylogenetic identification and in situ detection of individual microbial cells without cultivation. - Amann, R I (1995)
The frequent discrepancy between direct microscopic counts and numbers of culturable bacteria from environmental samples is just one of several indications that we currently know only a minor part of the diversity of microorganisms in nature. A combination of direct retrieval of rRNA sequences and whole-cell oligonucleotide probing can be used to detect specific rRNA sequences of uncultured bacteria in natural samples and to microscopically identify individual cells. Studies have been performed with microbial assemblages of various complexities ranging from simple two-component bacterial endosymbiotic associations to multispecies enrichments containing magnetotactic bacteria to highly complex marine and soil communities. Phylogenetic analysis of the retrieved rRNA sequence of an uncultured microorganism reveals its closest culturable relatives and may, together with information on the physicochemical conditions of its natural habitat, facilitate more directed cultivation attempts. For the analysis of complex communities such as multispecies biofilms and activated-sludge flocs, a different approach has proven advantageous. Sets of probes specific to different taxonomic levels are applied consecutively beginning with the more general and ending with the more specific (a hierarchical top-to-bottom approach), thereby generating increasingly precise information on the structure of the community. Not only do rRNA-targeted whole-cell hybridizations yield data on cell morphology, specific cell counts, and in situ distributions of defined phylogenetic groups, but also the strength of the hybridization signal reflects the cellular rRNA content of individual cells. From the signal strength conferred by a specific probe, in situ growth rates and activities of individual cells might be estimated for known species. In many ecosystems, low cellular rRNA content and/or limited cell permeability, combined with background fluorescence, hinders in situ identification of autochthonous populations. Approaches to circumvent these problems are discussed in detail.